Weight-height relationship in girls with normal body fat content - Turner's syndrome vs. healthy short-statured - Edyta Sienkiewicz-Dianzenza; Katarzyna Milde; Paweł Tomaszewski; Romuald Stupnicki (Pediatric Endocrinology, Diabetes and Metabolism)
Introduction: Turner’s syndrome is characterised by severely deficient body height and distorted body proportions as compared with healthy girls. It could be expected that shorter legs with respect to trunk length, together with a wider shoulder girdle, would disturb weight-height proportions. The aim of the study: To compare weight-height relation in Turner girls with that in healthy, short-statured girls, provided both had body fat content within “normal” limits. Material and methods: The study included 39 girls with Turner’s syndrome and 63 healthy short-statured girls aged 10-20 years. Body height, body mass and body fat content were determined. Data analysis was performed for only those girls whose body fat content was within approximate normal limits for age calculated for the purpose of presented study. Body height and body mass were transformed to logarithms in order to obtain allometric relations. Results: No significant differences were found between regression slopes what means that body mass was proportional to body height in both groups. On the other hand, regression constants differed significantly (p <0.001); Turner girls were, on average, by 11% heavier than their healthy mates. Conclusion: The selection of Turner and healthy, short-statured subjects with “normal” percentage of body fat content led to conclusion that increased relative body mass of Turner girls resulted from their specific body proportions and not from increased fat content.